2017
DOI: 10.18632/oncotarget.15552
|View full text |Cite
|
Sign up to set email alerts
|

Tumorigenesis promotes Mdm4-S overexpression

Abstract: Disruption of the p53 tumor suppressor pathway is a primary cause of tumorigenesis. In addition to mutation of the p53 gene itself, overexpression of major negative regulators of p53, MDM2 and MDM4, also act as drivers for tumor development. Recent studies suggest that expression of splice variants of Mdm2 and Mdm4 may be similarly involved in tumor development. In particular, multiple studies show that expression of a splice variant of MDM4, MDM4-S correlates with tumor aggressiveness and can be used as a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 30 publications
0
14
0
Order By: Relevance
“…Independently, the Lozano lab demonstrated that elevated MDM4-S transcript levels in tumors arise from splicing defects, rather than being selected for inherent oncogenic capacity. Consistently, MDM4-S protein levels did not accumulate in their transgenic MDM4-S B-cell lymphoma mouse model (Pant et al, 2017). It must be noted that these findings have been generated in mice, and variation between the murine and human MDM4 homologes exists (Shvarts et al, 1996).…”
Section: Regulation Of Mdm4 In Health and Diseasementioning
confidence: 70%
“…Independently, the Lozano lab demonstrated that elevated MDM4-S transcript levels in tumors arise from splicing defects, rather than being selected for inherent oncogenic capacity. Consistently, MDM4-S protein levels did not accumulate in their transgenic MDM4-S B-cell lymphoma mouse model (Pant et al, 2017). It must be noted that these findings have been generated in mice, and variation between the murine and human MDM4 homologes exists (Shvarts et al, 1996).…”
Section: Regulation Of Mdm4 In Health and Diseasementioning
confidence: 70%
“…Similar to MDM2 and P53, MDM4 also has an isoform frequently occurring in tumors, Mdm4-S, where exon 6 is excluded from the protein [245]. It has been demonstrated to be highly expressed in B-cell leukemia, for which it may potentially serve as a biomarker [257]. Although Mdm4-S is prone to nonsense-mediated decay, its degradation is obstructed in B-lymphocytes, which leads to elevated levels of this isoform [257,373].…”
Section: Summarizing Discussionmentioning
confidence: 99%
“…It has been demonstrated to be highly expressed in B-cell leukemia, for which it may potentially serve as a biomarker [257]. Although Mdm4-S is prone to nonsense-mediated decay, its degradation is obstructed in B-lymphocytes, which leads to elevated levels of this isoform [257,373]. This has been suggested to be the result of increased c-myc expression, which is overexpressed through amplification in many tumors [373,374].…”
Section: Summarizing Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Diexf is an evolutionarily conserved gene from yeast to humans, and recent studies in zebrafish have suggested that the Diexf protein is a negative regulator of p53 [ 9 , 15 ]. In many different human cancers with wild type TP53 , other TP53 inhibitors such as MDM2 and MDM4 are frequently amplified or overexpressed [ 8 , 21 ]. To ascribe a role of DIEXF in human cancers, we exploited the data from cBioPortal and examined whether a similar inverse correlation between TP53 and DIEXF exists [ 22 , 23 ].…”
Section: Resultsmentioning
confidence: 99%